Annoying Hiccups following Intra-Articular Corticosteroid Injection of Betamethasone Acetate/Betamethasone Sodium Phosphate at the Knee Joint - George Habib; Suheil Artul; Geries Hakim (Case Reports in Rheumatology)
Hiccups is a type of reflex that could happen secondary to different causes including drugs, especially systemic corticosteroids. Usually, high rather than regular doses of systemic steroids are incriminated, and this could explain the fact that very few cases of hiccups following regional corticosteroid treatment were reported. Here, we report the first case of hiccups in the English literature following intra-articular corticosteroid injection (IACI) at the knee joint and review all the previous reported cases of hiccups following regional corticosteroid treatment. Usually, this phenomenon of hiccups responds to regular antihiccups treatment; however, it is recommended not to repeat an IACI in a patient who had this adverse effect before due to an expected severe recurrent attack of hiccups afterwards.